Quantitative PCR detection of endangered diamond darter Crystallaria Cincotta in environmental DNA: employing locked nucleic acids and blocking probe for specificity - Andrew P. Kinziger; Cameron Layne; Stuart Welsh (Conservation Genetics Resources, 2025)

An experimental study of benthic habitat selection in yellow-phase American eels (Anguilla rostrata) - Melissa A. Braham; Stuart A. Welsh; Dustin M. Smith (Environmental Biology of Fishes, 2024)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genetic swamping and possible species collapse: tracking introgression between the native Candy Darter and introduced Variegate Darter - Isaac Gibson; Amy B. Welsh; Stuart A. Welsh; Daniel A. Cincotta (Conservation Genetics, 2019)

Variation in DNA methylation is associated with migratory phenotypes of lake sturgeon Acipenser fulvescens in the St. Clair River, MI, USA - Justine M. Whitaker; Amy B. Welsh; Darryl W. Hondorp; James C. Boase; George T. Merovich; Stuart Welsh; Charles Krueger (Journal of Fish Biology, 2018)
Lake sturgeon Acipenser fulvescens populations show a variety of movement patterns that are poorly understood. To compare two migratory phenotypes of A. fulvescens in the St. Clair River, MI, USA, multiple data types were analysed. Individual fish were classified into migratory phenotypes based on acoustic telemetry data collected 2012–2015. Acipenser fulvescens consistently showed movement from the St. Clair River upriver into Lake Huron or downriver into Lake St. Clair. The two migratory phenotypes were then compared for differences in morphometrics, genetics and epigenetics. Morphological differences based on linear measurements were not detected between phenotypes. Microsatellite data from 11 loci suggested one population with no genetic differentiation between migratory phenotypes. Our epigenetic results indicated that the migratory phenotypes are differentially methylated ( P A. fulvescens . Only one restriction site was identified to be driving the differential methylation ( P A. fulvescens , DNA methylation may play a role in the observed movement pattern variation. When combined with microsatellite and morphometric analyses, our results suggested that different migratory patterns may reflect phenotypic plasticity, allowing A. fulvescens to acclimate to short‐term environmental variability. Without an integrated approach, the role of epigenetics in the migratory phenotype of A. fulvescens may have been overlooked. Further characterization of migratory phenotypes could be important for management to conserve behavioural variation across the distribution of A. fulvescens and for design of stocking guidelines.

Diel periodicity and chronology of upstream migration in yellow-phase American eels (Anguilla rostrata) - Joni L. Aldinger; Stuart A. Welsh (Environmental Biology of Fishes, 2017)

Physical habitat and water quality correlates of crayfish distributions in a mined watershed - Stuart A. Welsh; Zachary J. Loughman (Hydrobiologia, 2015)

Advantages of Geographically Weighted Regression for Modeling Benthic Substrate in Two Greater Yellowstone Ecosystem Streams - Kenneth R. Sheehan; Michael P. Strager; Stuart A. Welsh (Environmental Modeling & Assessment, 2013)

Selection and preference of benthic habitat by small and large ammocoetes of the least brook lamprey (Lampetra aepyptera) - Dustin M. Smith; Stuart A. Welsh; Philip J. Turk (Environmental Biology of Fishes, 2011)

Response of benthic macroinvertebrate communities to highway construction in an Appalachian watershed - Lara B. Hedrick; Stuart A. Welsh; James T. Anderson; Lian-Shin Lin; Yushun Chen; Xinchao Wei (Hydrobiologia, 2010)

Threatened fishes of the world: Crystallaria cincotta Welsh and Wood 2008 (Percidae) - Stuart A. Welsh; Robert M. Wood; Kenneth R. Sheehan (Environmental Biology of Fishes, 2009)

Habitat partitioning in a community of darters in the Elk River, West Virginia - Stuart A. Welsh; Sue A. Perry (Environmental Biology of Fishes, 1998)